Taxonomic studies on Oriental Microplitis Foerster (Hymenoptera: Braconidae, Microgastrinae) with description of two new species from South India - Ranjith, A.p.; Rajesh, K.m.; Nasser, M. (Zootaxa, 2015)
The Oriental species of Microplitis Foerster are reviewed. 21 species are recognized from the Oriental region, of which two are described as new, Microplitis narendrani sp. nov. and M. pennatulae sp. nov., and Microplitis carinicollis (Cameron), M. demolitor Wilkinson, M. maculipennis (Szépligeti) and M. similis Lyle are redescribed. Four species, Microplitis areyongensis Austin & Dangerfield, M. bicoloratus Xu & He, M. vitellipedis Li, Tan & Song and M. zhaoi Xu & He are recorded for the first time from the Indian subcontinent. Host records are summarized. An illustrated key to the Oriental species is provided along with a character matrix to aid identification. Distributional pattern in Oriental region, host-parasitoid association and biology of the genus are critically summarized.